Menjadi Guru Iman Bagi Anak: Peran Orang Tua Dalam Katekese Keluarga - Angelina Febrianty Mukin; Intansakti Pius X (Jurnal Pendidikan Agama dan Teologi, 2024)
Parents are key in family catechesis. They became teachers of faith for their children. The family itself is the first and foremost place where children learn about faith. Parents have a responsibility to grow their children's faith and family catechesis is one way to do so. This study begins by discussing the importance of family catechesis. Then continued the role of parents as teachers of faith for their children. The study also presents some practical tips for parents on how they can teach their children about faith. The method used in this research is the descriptive qualitative method. The study concludes with the conclusion that family catechesis is a valuable tool that parents can use to help their children grow in faith and by following these tips, parents can be effective faith teachers for their children.